Gene regulatory and gene editing tools and their applications for retinal diseases and neuroprotection: From proof-of-concept to clinical trial - Altay, Halit Yusuf; Ozdemir, Fatma; Afghah, Ferdows; Kilinc, Zeynep; Ahmadian, Mehri; Tschopp, Markus; Agca, Cavit (Frontiers in Neuroscience, 2022)
Gene editing and gene regulatory fields are continuously developing new and safer tools that move beyond the initial CRISPR/Cas9 technology. As more advanced applications are emerging, it becomes crucial to understand and establish more complex gene regulatory and editing tools for efficient gene therapy applications. Ophthalmology is one of the leading fields in gene therapy applications with more than 90 clinical trials and numerous proof-of-concept studies. The majority of clinical trials are gene replacement therapies that are ideal for monogenic diseases. Despite Luxturna`s clinical success, there are still several limitations to gene replacement therapies including the size of the target gene, the choice of the promoter as well as the pathogenic alleles. Therefore, further attempts to employ novel gene regulatory and gene editing applications are crucial to targeting retinal diseases that have not been possible with the existing approaches. CRISPR-Cas9 technology opened up the door for corrective gene therapies with its gene editing properties. Advancements in CRISPR-Cas9-associated tools including base modifiers and prime editing already improved the efficiency and safety profile of base editing approaches. While base editing is a highly promising effort, gene regulatory approaches that do not interfere with genomic changes are also becoming available as safer alternatives. Antisense oligonucleotides are one of the most commonly used approaches for correcting splicing defects or eliminating mutant mRNA. More complex gene regulatory methodologies like artificial transcription factors are also another developing field that allows targeting haploinsufficiency conditions, functionally equivalent genes, and multiplex gene regulation. In this review, we summarized the novel gene editing and gene regulatory technologies and highlighted recent translational progress, potential applications, and limitations with a focus on retinal diseases.